Competence of Teachers to Support Special Needs Children in Our Dream Indonesia - Isra Al Aqsha; Mario Emilzoli (Eduvest - Journal of Universal Studies, 2024)
Education for children with special needs in Indonesia continues to face numerous challenges. Despite the increasing number of children with disabilities, resources to meet the needs of schools and institutions remain inadequate. This study aims to analyze the training needs of teaching staff to support the handling of children with disabilities at Our Dream Indonesia. The research is a case study with a qualitative descriptive approach. The study involved three managers and 21 accompanying teachers as informants. Open-ended questionnaires and interview forms were used as instruments. Qualitative descriptive analysis was employed as the data analysis technique. The collected data was divided into three parts: data reduction, data presentation, and conclusion drawing. The results indicated that children with disabilities at Our Dream Indonesia have diverse characteristics, including varying cognitive, physical, and social-emotional abilities. The teaching staff at Our Dream Indonesia requires training in several areas, including learning strategies for children with disabilities, educational technology, collaboration with parents and professionals, behavior management for children with disabilities, and implementation of the ABA method. The achievement of training can be measured through various methods, such as observation, tests, portfolios, and feedback. Therefore, Our Dream Indonesia should invest in training and professional development for teaching staff to ensure that children with disabilities receive a quality education that meets their needs.